If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(2n-4)-3=-36-3n
We simplify the equation to the form, which is simple to understand
5(2n-4)-3=-36-3n
Reorder the terms in parentheses
+(+10n-20)-3=-36-3n
Remove unnecessary parentheses
+10n-20-3=-36-3n
We move all terms containing n to the left and all other terms to the right.
+10n+3n=-36+20+3
We simplify left and right side of the equation.
+13n=-13
We divide both sides of the equation by 13 to get n.
n=-1
| -36-4a=-4(8a-5) | | 4x+3+4x=-15 | | 0=-8m^2-2m+2 | | -15s=-75 | | -3/2m+2/3m=-1/2(1/2m-3/2)-8/3(1/2m+1) | | x-(12)=-4 | | 2x+(2/(2x-12)) | | -7(4t+14)=-20-15t | | -7x=-28+11-4 | | y-19.25=x^2+6x+30.25 | | 3-x=2(1-4x)-6 | | 7t-12-2t=9+5t | | 2x+(2/2x-12) | | 2.5x+.5x=6+3.5 | | -(-20-4s)=-2(s+8) | | -8r=4(r-3) | | -50=19+y | | -5n-10=-(8n-1)-8n | | y=(x-2)-1 | | -(30)-(10)-43= | | 25200*(1/9) | | 80=1.8C+32 | | -255=-15k | | 10h=2(4h+13) | | 3a+9-6=21 | | 9.95m=m | | -3(x+5)=-3x-15 | | -18+2(j-12)=-12j | | 25200*(1/10) | | 4.95m+49.95=m | | -0.75x-2=0.25x | | y-6=-5/4(x+1) |